Related Articles
Class 10 RD Sharma Solutions – Chapter 9 Arithmetic Progressions – Exercise 9.2
• Last Updated : 08 Dec, 2020

### Problem 1: Show that the sequence defined by an = 5n – 7 is an A.P., find its common difference.

Solution:

Given:

an = 5n – 7

Now putting n = 1, 2, 3, 4,5 we get,

a1 = 5.1 – 7 = 5 – 7 = -2

a2 = 5.2 – 7 = 10 – 7 = 3

a3 = 5.3 – 7 = 15 – 7 = 8

a4 = 5.4 – 7 = 20 – 7 = 13

We can see that,

a2 – a1 = 3 – (-2) = 5

a3 – a2 = 8 – (3) = 5

a4 – a3 = 13 – (8) = 5

Since, the successive difference of list is same i.e 5

∴ The given sequence is in A.P and have common difference of 5

### Problem 2: Show that the sequence defined by an = 3n2 – 5 is not an A.P.

Solution:

Given:

an = 3n2 – 5

Now putting n = 1, 2, 3, 4 we get,

a1 = 3.1.1 – 5= 3 – 5 = -2

a2 = 3.2.2 – 5 = 12 – 5 = 7

a3 = 3.3.3 – 5 = 27 – 5 = 22

a4 = 3.4.4 – 5 = 48 – 5 = 43

We can see that,

a2 – a1 = 7 – (-2) = 9

a3 – a2 = 22 – 7 = 15

a4 – a5 = 43 – 22 = 21

Since, the successive difference of list is not the same

∴ The given sequence is not in A.P

### Problem 3: The general term of a sequence is given by an = -4n + 15. Is the sequence an A.P.? If so, find its 15th term and the common difference.

Solution:

Given:

an = -4n + 15

Now putting n = 1, 2, 3, 4 we get,

a1 = -4.(1) + 15 = -4 + 15 = 11

a2 = -4.(2) + 15 = -8 + 15 = 7

a3 = -4.(3) + 15 = -12 + 15 = 3

a4 = -4.(4) + 15 = -16 + 15 = -1

We can see that,

a2 – a1 = 7 – (11) = -4

a3 – a2 = 3 – 7 = -4

a4 – a3 = -1 – 3 = -4

Since, the successive difference of list is same i.e -4

∴ The given sequence is in A.P and have common difference of -4

Hence, the 15th term will be

a15 = -4(15) + 15 = -60 + 15 = -45

And, a15 = -45

### (i) an = 3 + 4n

Solution:

Given:

an = 3 + 4n

Now putting n = 1, 2, 3, 4 we get,

a1 = 3 + 4.1 = 7

a2 = 3 + 4.2 = 11

a3 = 3 + 4.3 = 15

a4 = 3 + 4.4 = 19

∴ The sequence is 7, 11, 15, 19

We can see that,

a2 – a1 = 11 – (7) = 4

a3 – a2 = 15 – (11) = 4

a4 – a3 = 19 – (15) = 4

Since, the successive difference of list is same i.e 4

∴ The given sequence is in A.P

### (ii) an = 5 + 2n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 5 + 2.1 = 7

a2 = 5 + 2.2 = 9

a3 = 5 + 2.3 = 11

a4 = 5 + 2.4 = 13

∴ The sequence is 7, 9, 11, 13

We can see that,

a2 – a1 = 9 – (7) = 2

a3 – a2 = 11 – (9) = 2

a4 – a3 = 13 – (11) = 2

Since, the successive difference of list is same i.e 2

∴ The given sequence is in A.P

### (iii) an = 6 – n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 6 – 1 = 5

a2 = 6 – 2 = 4

a3 = 6 – 3 = 3

a4 = 6 – 4 = 2

∴ The sequence is 5, 4, 3, 2

We can see that,

a2 – a1 = 4 – (5) = -1

a3 – a2 = 3 – (4) = -1

a4 – a3 = 2 – (3) = -1

Since, the successive difference of list is same i.e -1

∴ The given sequence is in A.P

### (iv) an = 9 – 5n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 9 – 5.1 = 4

a2 = 9 – 5.2 = -1

a3 = 9 – 5.3 = -6

a4 = 9 – 5.4 = -11

∴ The sequence is 4, -1, -6, -11

We can see that,

a2 – a1 = -1 – (4) = -5

a3 – a2 = -6 – (-1) = -5

a4 – a3 = -11 – (-6) = -5

Since, the successive difference of list is same i.e -5

∴ The given sequence is in A.P

### Problem 5: The nth term of an A.P. is 6n + 2. Find the common difference.

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 6.1 + 2 = 8

a2 = 6.2 + 2 = 14

a3 = 6.3 + 2 = 20

a4 = 6.4 + 2 = 26

We can see that,

a2 – a1 = 14 – (8) = 6

a3 – a2 = 20 – (14) = 6

a4 – a3 = 26 – (20) = 6

Hence, the common difference is 6

### (i) an = 2n – 1

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 2.1 – 1 = 1

a2 = 2.2 – 1 = 3

a3 = 2.3 – 1 = 5

a4 = 2.4  – 1 = 7

We can see that,

a2 – a1 = 3 – (1) = 2

a3 – a2 = 5 – (3) = 2

a4 – a3 = 7 – (5) = 2

Since, the successive difference of list is same i.e 2

Hence, the given sequence is in A.P

### (ii) an = 3n² + 5

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 3.1.1 + 5 = 8

a2 = 3.2.2 + 5 = 17

a3 = 3.3.3 + 5 = 32

a4 = 3.4.4 + 5 = 53

We can see that,

a2 – a1 = 17 – (8) = 9

a3 – a2 = 32 – (17) = 15

a4 – a3 = 53 – (32) = 21

Since, the successive difference of list is not the same

Hence, the given sequence is not in A.P

### (iii) an = 1 + n + n²

Solution:

Now putting n = 1, 2, 3 we get,

a1 = 1 + 1 + 1.1 = 3

a2 = 1 + 2 + 2.2 = 7

a3 = 1 + 3 + 3.3 = 13

We can see that,

a2 – a1 = 7 – (3) = 4

a3 – a2 = 13 – (7) = 6

Since, the successive difference of list is not the same

Hence, the given sequence is not in A.P

Attention reader! Don’t stop learning now. Get hold of all the important DSA concepts with the DSA Self Paced Course at a student-friendly price and become industry ready.

My Personal Notes arrow_drop_up